Evaluasi Kebijakan Pajak Penghasilan atas Pembayaran Bunga Pinjaman pada Transaksi Peer To Peer Lending Berdasarkan Prinsip Good Tax Policy - Vidina Diniarti Hanifa; Haula Rosdiana (Syntax Idea)
Based on the results of the researcher's previous study, there are several issues arising from tax deductions referring to Law Number 36 of 2008 regarding the Fourth Amendment to Law Number 7 of 1983 regarding Income Tax. In the midst of the researcher's study, a new law was enacted, namely Law Number 7 of 2021 concerning Tax Regulation Harmonization (TRH Law), which was further regulated in the Minister of Finance Regulation Number 69 of 2022 concerning Income Tax and Value Added Tax on Financial Technology Peer-to-Peer Lending Activities. Therefore, an evaluation is needed regarding the Income Tax policy in financial technology peer-to-peer lending interest payment transactions. This research was conducted using a quantitative approach (deductive logic), qualitative data collection techniques, and qualitative data analysis techniques. The results of this study indicate that Law Number 36 of 2008 regarding the Fourth Amendment to Law Number 7 of 1983 regarding Income Tax Article 23 is considered to not provide legal certainty for peer-to-peer lending interest payment transactions, resulting in increased compliance costs, and a lack of administrative simplicity. With the enactment of Law Number 7 of 2021 concerning Tax Regulation Harmonization, legal certainty regarding tax regulations on fintech peer-to-peer lending interest payment transactions has become clearer and more straightforward. In terms of compliance costs, this policy shift has only transferred the withholding obligation burden from the borrower's side to the platform provider. However, overall, the TRH Law and Minister of Finance Regulation Number 69 have accommodated peer-to-peer lending transactions more effectively.